Application of research reactor environments for validation of the IRDFF-II dosimetry cross section library - Griffin Patrick; Peters Curtis; Parma Edward; Vehar David (EPJ Web of Conferences)
Activation data from seven different reactor-based reference neutron fields are examined to provide enhanced validation evidence for the newly released IRDFF-II library. A least-squares based spectrum adjustment methodology is used and rigorous statistical metrics demonstrate the consistency of the set of IRDFF-II dosimetry cross sections. The use of these reactor-based neutron fields provides validation evidence for nine more reactions than have been addressed in the 252Cf(sf) and 235U(th) benchmark validation testing. The use of covers to shift their energy response increases the power of the response validation but makes it challenging to properly capture response correlations.